COOPERATIVAS AGROPECUÁRIAS NO MERCOSUL: UM ENSAIO SOBRE AS ESTRATÉGIAS DE INTERNACIONALIZAÇÃO - Jones, Hilary; Bialoskorski Neto, Sigismundo (Brazilian Journal of Latin American Studies, 2008)
This work evaluates the importance of internationalization strategies for agricultural cooperatives in the MERCOSUL. A discussion of barriers to the internationalization of cooperatives is also presented, such as spatial/geographic contradictions – delocalization in cooperatives — finance difficulties, governance, and cultural problems. Next, all the possible options are given in the Export/Import, Foreign Direct Investment, and Commercial Agreements. The article concludes by noting that despite the difficulties of creating international cooperative systems, the construction of farmer-owned international business agreements and structures, thought cooperatives organization, holds promise for assuring survival of small scale producers, combating trends that decrease margins for primary product producers.